Partitioning QoS management for secure tactical wireless ad hoc networks. - Elmasry, George F.; McCann, C. John.; Welsh, Robert
Addressing quality of service in military wireless ad hoc communication networks involves unique challenges due to imposed tactical requirements and,conditions, such as heterogeneous traffic with stringent-real-time and survivability requirements, mobile wireless nodes in hostile environments, and limited spectrum availability. Encryption adds another layer of complexity because of the partitioning of the network into plain text (unencrypted) and cipher text (encrypted) parts that, by definition, cannot communicate QoS information to one another. A typical communication shelter is composed of unencrypted LANs connected to a packet-encrypted backbone network. This article presents a partitioned QoS approach, focusing on QoS management at the unencrypted LAN that complements QoS management done at the encrypted backbone. Some of the unencrypted LAN QoS techniques being considered for the Warfighter Information Network-Tactical (the future Army tactical backbone network) are outlined.
Keywords: QoS management; cipher text; encryption; military wireless ad hoc communication network; packet-encrypted backbone network; plain text; quality of service; tactical wireless ad hoc networks security; unencrypted LAN; warfighter information network-tactical.